Impact of an exceptional winter flood on benthic oxygen and nutrient fluxes in a temperate macrotidal estuary: Potential consequences on summer deoxygenation - Hulot, Vivien; Metzger, Edouard; Thibault de Chanvalon, Aubin; Mouret, Aurelia; Schmidt, Sabine; Deflandre, Bruno; Rigaud, Sylvain; Beneteau, Eric; Savoye, Nicolas; Souchu, Philippe; Le Merrer, Yoann; Maillet, Grégoire M. (Frontiers in Marine Science, 2023)
Despite 20 years of control on eutrophication, episodes of summer hypoxia still occur in the Loire estuary, impacting water quality and posing a key scientific and management challenge. This work aimed to quantify the contribution of the benthic compartment to hypoxia in the Loire estuary by direct measurement of water–sediment fluxes and an in-depth understanding of the seasonal variations of oxides and phosphorus stocks. During the summer’s low-discharge period, results show that the iron oxide-rich deposit is stable under hypoxic conditions, limiting the release of dissolved phosphorus into the overlying water column. The high nitrate content of the water column appears to be an important oxidizer of iron during hypoxic periods, limiting dissolved phosphorus leakage and aggravation of hypoxia. During the exceptional winter flood, significant sediment erosion associated with bubbling phenomena (attributed to methane efflux) created severe fractures in the sediment and stimulated water–sediment exchange. During the following months, these fractures were progressively filled, which decreased the intensity of benthic fluxes. However, due to the high residence time in the water during the summer period, a simple model demonstrated that benthic contributions were sufficient to directly (by direct oxygen consumption) or indirectly (by promoting ammonia oxidation) affect the oxygen stock in the water column during the low-discharge period. Our study demonstrates the importance of the benthic compartment in the occurrence of hypoxia and the obvious lack of knowledge to illustrate and model the biogeochemical functioning of the estuary.